Conceptual Issues in Calibrating the Basel III Countercyclical Capital Buffer - Wezel, Torsten (Washington, D.C. : International Monetary Fund, 2019)
This paper discusses issues in calibrating the countercyclical capital buffer (CCB) based on a sample of EU countries. It argues that the main indicator for buffer decisions under the Basel III framework, the credit-to-GDP gap, does not always work best in terms of covering bank loan losses that go beyond what could be expected from economic downturns. Instead, in the case of countries with short financial cycles and/or low financial deepening such as transition and developing economies, the Basel gap is shown to work best when computed with a low, smoothing factor and adjusted for the degree of financial deepening. The paper also analyzes issues in calibrating an appropriate size of the CCB and, using a loss function approach, points to a tradeoff between stability of the buffer size and cost efficiency considerations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet